Joseph Grzywaczewski, Great Persecutions and the Reconciliation of the Lapsi, Warszawa 2015, Wydawnictwo Uniwersytetu Kardynała Stefana Wyszyńskiego, ss. 162. - Szczur, Piotr (Vox Patrum, 2018)
nie dotyczy